2023
DOI: 10.1002/cbdv.202201059
|View full text |Cite
|
Sign up to set email alerts
|

Furo[2,3‐d]pyrimidines as Mackinazolinone/Isaindigotone Analogs: Synthesis, Modification, Antitumor Activity, and Molecular Docking Study

Abstract: The chemical transformation of the tricyclic furo[2,3‐d]pyrimidines was performed under isosteric and scaffold‐hopping strategies focusing on the synthesis of its arylidene and imine‐containing derivatives. Naturally‐occurring alkaloids mackinazolinone and isaindigotone were as templates of target heterocycles. Synthesized compounds evaluated for their antitumor activity on human cancer cervical HeLa, breast MCF‐7, and colon HT‐29 cell lines. Four compounds: 8c, 8e, 10b, and 10c demonstrated potency against He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Among them, two compounds V and VII showed potency against HeLa and HT‐29 with IC50 values ranging from 7.37 μM to 13.72 μM. Molecular docking results indicated that compounds V and VII exhibited good binding and high matching with the target EGFR protein [31] . Moreover, The research by Mousavi et al.…”
Section: Biological Activity and Applicationsmentioning
confidence: 95%
See 2 more Smart Citations
“…Among them, two compounds V and VII showed potency against HeLa and HT‐29 with IC50 values ranging from 7.37 μM to 13.72 μM. Molecular docking results indicated that compounds V and VII exhibited good binding and high matching with the target EGFR protein [31] . Moreover, The research by Mousavi et al.…”
Section: Biological Activity and Applicationsmentioning
confidence: 95%
“…Molecular docking results indicated that compounds V and VII exhibited good binding and high matching with the target EGFR protein. [31] Moreover, The research by Mousavi et al (2023) presents a green and efficient method for the synthesis of drug-like furo[2,3-d]pyrimidines. These compounds were tested for their inhibitory properties against both SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2) MPro (Main Protease) and PLPro (Papain-Like Protease).…”
Section: Biological Activity and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research team has been dedicated to developing diverse antitumor compounds integrated with tricyclic heterocycles [3], and have achieved encouraging results [4] using natural products such as deoxyvasicinone [5] and mackinazolinone as templates. The benzene ring structure in quinazoline was replaced with a fivemembered heterocyclic ring, and eight new tricyclic heterocyclic pyrimidines were synthesized based on principles of electron isosteric and skeletal transition in drug design [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%